A Simple Method of Producing Hydroxyapatite and Tri Calcium Phosphate from Coral (Pocillopora verrucosa) - (:unkn) unknown (SPRINGER, 2014)
Hydroxyapatite (HA) has been widely used as a biocompatible ceramic in biomedical engineering applications in the past few decades. This paper reports on the preparation of hydroxyapatite and triaclium-phosphate (TCP) from a coral source using a simple mechanochemical method. Coral materials are made of calcium carbonate in the form of aragonite. Coral source materials were assessed using thermogravimetric and differential thermal analysis (TG/DTA). The resulting HA and TCP powders obtained were without any impurities. At two different elevated temperatures (of 400 and 800 degrees C) the coral was converted to HA and TCP materials. Scanning electron microscope (SEM), X-ray diffraction (XRD) and Fourier transform infrared (FTIR) studies were performed.
Keywords: hydroxyapatite; tricalcium phosphate; coral; biomimetic; bioceramics; mechanochemical method; TOOTH-HYDROXYAPATITE; POWDERS